How Does Organization Network and Market Orientation Affect Marketing Performance? Case of PTPN IX Downstream Products, Central Java - Wahyudi, Wahyudi; Heridiansyah, Jefri; Susetyarsi, Theresia; Safari, Teti; Prabowo, Catur (Management Analysis Journal, 2024)
This  study  aims  to  determine  the  effect  of  organizational  network  and  market orientation  on  marketing  performance  on  downstream  products  of  PTPN  IX Central  Java.  The  sample  is  34  respondents  with  a  nonprobability  sampling technique using the census method. The  independent variables in this study are organizational  networks  and  market  orientation,  then  the  dependent variable  is marketing  performance.  The  data  collection   method  used  in  this  study  is  a questionnaire. The data analysis method used is descriptive analysis and multiple linear regression analysis. Based on the research results, organizational networks   positively   and   significantly   affect   marketing   performance.   The   market orientation has a positive and significant effect on the marketing performance of downstream  products  of  PTPN  IX  in  Central  Java.  Marketing  performance impacts  sales  turnover,  sales  increase  and  marketing  reach.  Therefore, management must pay attention to every relationship, whether friends, business relations  or  partner  companies,  both  large  and  small,  and  fulfill  customer orientation, threats from competitors, and market information.